O núcleo de apoio à saúde da família (NASF) como mobilizador da práxis psicossocial - Moura, Renata Heller de [UNESP] (2014)
For over three decades the brazilian psychiatric reform in line with health reform, is allowing us to see that the struggle for deinstitutionalization “insanity” is done not only by the “overthrow of the walls” of the psychiatric hospital, but also the struggle for “tear down the walls” of institutionalization that submits to all of us. The creation of extra-hospital devices is a major breakthrough in this process. However, alone, these devices do not guarantee the deconstruction of fragmented medicalizadoras and ineffective interventions. More than the creation of devices and programs, we need a networking developed from primary care by many devices for health care, mobilized by psychosocial practice. This research presents the Family Health Support Center (FHSC) as a resonance of the intertwining of reform movements in the health field in Brazil (health and psychiatric reforms). The FHSC is a program of the Ministry of Health, established in 2008, aiming to strengthen and broaden the scope of action of the Family Health Strategy, thus helping to catalyze the reorientation of the health care model in this country. Our interest was to investigate it as a device capable of mobilizing psychosocial practice and contribute to the development of mental health care within Primary Care. To this end, we seek to meet the proposals and actions taken by a professional FHSC in an inland city of Paraná. The research lies in the field of qualitative methodologies and has its methodological orientation guided by the concept of man as a historic, able to transform reality and be transformed by it, in a constant interaction with the social environment and the material world to be. From this methodological orientation, we use the concept of “praxis”, understanding it as a substantive activity of the human being who acts in history, causing changes that outweigh the social settings and trying to break through the repetitive practice to ...